The age‐related incidence of male genital lichen sclerosus is triphasic - Cherry Choudhary; Ryan Beazley; Encarl Uppal; Georgios Kravvas; Christopher Bunker (Wiley, 2024)
Abstract Background Male genital lichen sclerosus (MGLSc) is a chronic and acquired inflammatory dermatosis associated with substantial sexual dysfunction and urological morbidity and mortality. The age incidence of MGLSc is held to be biphasic, with a peak in infancy and another in adulthood. A recent review has implied two peaks in adulthood (making it triphasic overall); this triphasicity has been our emergent clinical impression from a voluminous practice. Furthermore, a link between MGLSc and smoking has been suggested, but this has not been our clinical impression. Objectives The primary objective was to clarify the age‐specific incidence of adult men with GLSc; the secondary objective was to explore the relationship between MGLSc and smoking. Methods We retrospectively reviewed the medical notes of 487 adult MGLSc patients from a large specialist male genital dermatology clinic. We abstracted data about the age of diagnosis and smoking history. Results A biphasic U‐shaped age distribution was identified with two clear peaks at the end of the third decade and another in the sixth decade of life (Hartigan's dip‐stat = 0.03; p < 0.01). Thirty‐six percent of the patients had been smokers at some point in their lives. Conclusions These findings confirm that MGLSc is biphasic in its adult incidence, confirming an earlier supposition; including the previously well‐acknowledged paediatric peak, it is thus triphasic. The smoking data are probably unremarkable compared with the available data for smoking habits from the United Kingdom. These findings indirectly support what is postulated about the likely pathogenesis of MGLSc, that is, urinary micro‐incontinence, occlusion and epithelial susceptibility.